Stability in a mathematical model for HIV”“1 infection - Ortega, Horacio; Martín Landrove, Miguel; González, Jorge (Ciencia)
We extend a previous epitope model for HIV-1 infection originally developed by Nowak et al. (1995) by considering not only continually mutant free virions but also viral reservoirs as monocytes. The immunological system response to viral infections includes the attack to monocytes by specific cytotoxic cells addressed against each one of the exhibiting epitope monocytes and the removal of free viral particles by T cell mediated interactions. We obtain a non lineal system of equations that allows only numerical treatment. Under the additional hypothesis that there is no immune attack to monocytes and only a viral variant, we got a simpler model that admits the usual linearization procedure. The inclusion of immune attack against infected monocytes in general stabilizes previously unstable solutions, but if new viral variants appear the system becomes unstable. These results suggest that the whole role played by reservoirs in HIV infection is a very important one and therapy should not go on ignoring it.